2022
DOI: 10.1002/cncr.34174
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and systemic inflammation are associated with decreased survival after cytoreductive nephrectomy for metastatic renal cell carcinoma

Abstract: BACKGROUND:This study was aimed at assessing the associations of sarcopenia, muscle density, adiposity, and inflammation with overall survival (OS) after cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma. METHODS: In all, 158 patients undergoing CN from 2001 to 2014 had digitized preoperative imaging for tissue segmentation via Slice-O-Matic software (version 5.0) at the mid-L3 level. The skeletal muscle index was calculated with the skeletal muscle area (cm 2 ) normalized for height (m 2 ), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…BMI has previously been regarded as a prognostic indicator of tumors. In this paper, sarcopenia was found associated with a low BMI, while multivariable analysis revealed that BMI was not an independent predictor for OS, which was in agreement with prior studies examining BMI and RCC ( 15 , 22 ). However, a recent research pointed out that longer survival occurred in patients with higher BMI, and it was restricted to males, but not to females ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…BMI has previously been regarded as a prognostic indicator of tumors. In this paper, sarcopenia was found associated with a low BMI, while multivariable analysis revealed that BMI was not an independent predictor for OS, which was in agreement with prior studies examining BMI and RCC ( 15 , 22 ). However, a recent research pointed out that longer survival occurred in patients with higher BMI, and it was restricted to males, but not to females ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…( 14 ) found the combined utility of sarcopenia and the elevated mGPS for predicting reduced survival and earlier recurrence in patients with localized RCC. Sarcopenia with elevated NLR or CRP as a negative predictor of OS after cytoreductive nephrectomy in metastatic RCC was later investigated ( 15 ). Similarly, the poor prognostic effects of sarcopenia and NLR in colorectal cancer ( 11 ), as well as sarcopenia and LMR in gastric cancer ( 13 ) have explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative axial CT and MRI images were segmented at the mid-L3 vertebral level as previously described. [ 1 , 2 ] Imaging segmentation was completed by 4 trained observers following training requiring <1% inter-observer and intra-observer variability. Each observer was blinded to patient history and outcomes.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Image processing was completed using Slice-O-Matic software (version 5.0; Tomovision) using predesignated thresholds for skeletal muscle (-29 to +150 Hounsfield units for CT and region growing tool for MRI). [1] , [2] , [3] , [4] Skeletal muscle area (SMA) in cm 2 was determined by measuring the combined surface area of the psoas, quadratus lumborum, erector spinae, transversus abdominis, internal oblique, external oblique, and rectus abdominis. Skeletal muscle index (SMI; cm 2 /m 2 ) was calculated by normalizing the SMA by height in meters squared.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%